Clinicopathological analysis of colorectal cancer: a comparison between emergency and elective surgical cases - Ghazi, Sam (BioMed Central, 2013)
BACKGROUND: Approximately 15 to 30% of colorectal cancers present as an emergency, most often as obstruction or perforation. Studies report poorer outcome for patients who undergo emergency compared with elective surgery, both for their initial hospital stay and their long-term survival. Advanced tumor pathology and tumors with unfavorable histologic features may provide the basis for the difference in outcome. The aim of this study was to compare the clinical and pathologic profiles of emergency and elective surgical cases for colorectal cancer, and relate these to gender, age group, tumor location, and family history of the disease. The main outcome measure was the difference in morphology between elective and emergency surgical cases. METHODS: In total, 976 tumors from patients treated surgically for colorectal cancer between 2004 and 2006 in Stockholm County, Sweden (8 hospitals) were analyzed in the study. Seventeen morphological features were examined and compared with type of operation (elective or emergency), gender, age, tumor location, and family history of colorectal cancer by re-evaluating the histopathologic features of the tumors. RESULTS: In a univariate analysis, the following characteristics were found more frequently in emergency compared with elective cases: multiple tumors, higher American Joint Committee on Cancer (AJCC), tumor (T) and node (N) stage, peri-tumor lymphocytic reaction, high number of tumor-infiltrating lymphocytes, signet-ring cell mucinous carcinoma, desmoplastic stromal reaction, vascular and perineural invasion, and infiltrative tumor margin (P<0.0001 for AJCC stage III to IV, N stage 1 to 2/3, and vascular invasion). In a multivariate analysis, all these differences, with the exception of peri-tumor lymphocytic reaction, remained significant (P<0.0001 for multiple tumors, perineural invasion, infiltrative tumor margin, AJCC stage III, and N stage 1 to 2/3). CONCLUSIONS: Colorectal cancers that need surgery as an emergency case generally show a more aggressive histopathologic profile and a more advanced stage than do elective cases. Essentially, no difference was seen in location, and therefore it is likely there would be no differences in macro-environment either. Our results could indicate that colorectal cancers needing emergency surgery belong to an inherently specific group with a different etiologic or genetic background.